Probing surface and interface structure using optics - MCGILP, JOHN (My University, 2010)
Optical techniques for probing surface and interface structure are introduced and recent developments in the field are discussed. These techniques offer significant advantages over conventional surface probes: all pressure ranges of gas?condensed matter interfaces are accessible and liquid?liquid, liquid?solid and solid?solid interfaces can be probed, due to the large penetration depth of the optical radiation. Sensitivity and discrimination from the bulk are the two challenges facing optical techniques in probing surface and interface structure. Where instrumental improvements have resulted in enhanced sensitivity, conventional optical techniques can be used to characterize heterogeneous adsorbed layers on a substrate, often with sub-monolayer resolution. Nanoscale lateral resolution is possible using scanning near-field optics. A separate class of techniques, which includes reflection anisotropy spectroscopy, and nonlinear optical probes such as second-harmonic and sum-frequency generation, uses the difference in symmetry between the bulk and the surface or interface to suppress the bulk contribution. A perspective is presented of likely future developments in this rapidly expanding field.
PUBLISHED
Keywords: Condensed matter physics; Optics; Nanoscience & Materials